Development of global rating instruments for pediatric patients with ataxia telangiectasia. (January 2016) - Nissenkorn, Andreea; Borgohain, Rupam; Micheli, Roberto; Leuzzi, Vincenzo; Hegde, Anaita Udwadia; Mridula, Kandadai Rukmini; Molinaro, Anna; D'Agnano, Daniela; Yareeda, Sireesha; Ben-Zeev, Bruria
Abstract: Introduction: Ataxia telangiectasia (AT) is a neurodegenerative disorder with cerebellar and extrapyramidal features. Interventional and epidemiological studies in AT should rely on specific scales which encompass the specific neurological features, as well the early progressive course and the subsequent plateau. The aim of this study was to build a scale of the CGI type (Clinical Global Impression) which is disease specific, as well as to check the feasibility of the ICARS scale for ataxia in this population. Methods: We recruited 63 patients with ataxia, aged 10.76 ± 3.2 years, followed at 6 international AT centers, 49 of them (77.8%) with classical AT. All patients were evaluated for ataxia with ICARS scale. In patients with AT, two CGI scales were scored, unstructured as structured for which separate anchors were provided. Results: Mean ICARS score was 44.7 ± 20.52, and it's severity positively correlated with age (Spearman correlation, r = 0.46, p < 0.01). Mean CGI score was 2 (moderately involved). There was a high correlation between the structured and unstructured CGIs (Spearman correlation, r = 0.87, p < 0.01). Both CGI scales showed positive correlation between severity and increasing age (Spearman correlation r = 0.59, p < 0.01 for structured CGI and r = 0.61, p < 0.01 for unstructured). Discussion: We succeeded to build two CGI scales: structured and unstructured, which are disease specific for AT. The unstructured scale showed better connection to disease course; the sensitivity of the unstructured scale could be improved by adding anchors related to extrapyramidal features. In addition we showed that ataxia can be reliably measured in children with AT by using ICARS. Highlights: Ataxia telangiectasia (AT) is a neurodegenerative disorder with cerebellar and extrapyramidal features. Interventional studies in AT need scales encompassing specific neurologic features, early progressive course and subsequent plateau. We build two Clinical Global Impression of severity scales (CGI-s): structured and unstructured, disease specific for AT. The unstructured scale defined better disease course; adding anchors related to extrapyramidal features should improve the sensitivity. Ataxia can be reliably measured in children with AT by using ICARS, as well as SARA or BARS scales.